Framework development for the assessment of interprofessional teamwork in mental health settings. Issue 1 (2nd January 2017) - Tomizawa, Ryoko; Shigeta, Masahiro; Reeves, Scott
ABSTRACT: In mental health settings, interprofessional practice is regarded as a comprehensive approach to prevent relapse and manage chronic conditions with practice of various teamwork interventions. To reinforce the potential of interprofessional teamwork, it is recommended that theories or conceptual frameworks be employed. There continues, however, to be a limited use of such approaches that assess the quality of interprofessional teamwork in mental health settings. This article aimed to present a new conceptual framework for the assessment of interprofessional teamwork based on the findings of a scoping review of the literature. This review was undertaken to identify conceptual frameworks utilised in interprofessional teamwork in mental health settings. After reviewing 952 articles, the methodological characteristics extracted from 12 articles were considered. The included studies were synthesised into the Donabedian structure-process-outcome model. The findings revealed that structural issues comprised three elements: professional characteristics, client-care characteristics, and contextual characteristics in organisations. Process issues comprised two elements: team mechanisms and community-oriented services. Finally, outcome issues comprised the following elements: clients' outcomes and professionals' outcomes. The review findings suggested possibilities for further development of how to assess the quality of interprofessional teamwork and provided information about what specific approach is required to improve interprofessional teamwork. Future research should utilise various areas and cultures to clarify the adaptation potential.